The Contours of Locke’s General Substance Dualism - Graham Clay (Journal of Modern Philosophy, 2022)
In this paper, I will argue that Locke is a substance dualist in the general sense, in that he holds that there are, independent of our classificatory schema, two distinct kinds of substances: wholly material ones and wholly immaterial ones. On Locke’s view, the difference between the two lies in whether they are solid or not, thereby differentiating him from Descartes. My way of establishing Locke as a general substance dualist is to be as minimally committal as possible at the outset, especially with respect to the classic debates on Locke’s positions in this domain, including those concerning substrata, real essences, and the like. Nonetheless, I show that minimal commitments about Locke’s primary/secondary quality distinction are sufficient to derive some substantive conclusions about his positions on these issues, as well as that he is a general substance dualist.